Análise de crescimento e conversão da energia solar em populações de milho (Zea mays L.) em Viçosa, Minas Gerais - Fernandes Lopes, Nei; Maestri, Moacyr (Revista Ceres, 2025)
Growth analysis and evaluation of efficiency of solar energy conversion were carried out with corn, in an agronomicoculture system.